Chemical and Nutrient Composition of Cookies Enriched with Pineapple Pomace and Ragi Flour - K. Hita; Deepti Patel; Prabhakar Singh; Hemant Kumar Panigrahi; Laxmanee; Priyanka P; Aaisha Nasim; Shweta Jangam; Swati Shukla (Archives of Current Research International, 2025)
The increasing demand for functional foods has led to the incorporation of fruit processing by-products and nutrient-dense cereals into conventional products. The purpose of this study was to assess the chemical composition of cookies made by substituting refined wheat flour (WF) with varied amounts of pineapple pomace powder (PPP) and ragi flour (RF). Six formulations, including a control (T₀ to T₅) were made: T₀ (100% WF), T₁ (5% PPP+ 85 % WF +10%RF), T2 (10% PPP+ 80 % WF +10%RF), T3 (15% PPP+ 75 % WF +10%RF) T4 (20% PPP+ 70 % WF +10%RF) and T5 (25% PPP+ 65 % WF +10% RF). Moisture, protein, fat, total sugar, non-reducing sugar, and reducing sugar were among the chemical characteristics that were examined. The results indicated that the treatments varied significantly (p<0.05). As PPP and RF levels increased, the moisture content increased as well. The protein content significantly increased, with T₅ displaying the highest value in comparison to the control. Although the differences were small, the fat content dropped with increasing PPP, from (T0) to (T₅). While in sugar percent, it was observed that Total sugar and non-reducing sugar content decreased over an increase in PPP content, whereas reducing sugar increased from (T₀) to (T₅).